operação com fração algébrica. PFVR ME AJUDEM
Anexos:
![](https://pt-static.z-dn.net/files/da0/9a9a75f9e8e730141bf2f7b87790feb6.jpg)
Soluções para a tarefa
Respondido por
1
Ola Vics
2a/(x - 3) + a/x - 2ax/(x*(x - 3))
2ax/(x*(x - 3)) + a*(x - 3)/(x*(x - 3)) - 2ax/(x*(x - 3)) =
(2ax + ax - 3a - 2ax)/(x*(x - 3) = a*(x - 3)/(x*(x - 3) = a/x
produto
(a/x)*(2a/x) = 2a²
.
2a/(x - 3) + a/x - 2ax/(x*(x - 3))
2ax/(x*(x - 3)) + a*(x - 3)/(x*(x - 3)) - 2ax/(x*(x - 3)) =
(2ax + ax - 3a - 2ax)/(x*(x - 3) = a*(x - 3)/(x*(x - 3) = a/x
produto
(a/x)*(2a/x) = 2a²
.
Perguntas interessantes
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás